2003
DOI: 10.1111/j.0306-686x.2003.05444.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Parameter Time Series Estimation of the Ohlson Model: Linear and Nonlinear Analyses

Abstract: This paper tests the empirical validity of the Ohlson (1995) model on a firm-level time series basis. The coefficients of the earnings dynamic and valuation equations are first estimated by OLS. Next, recognizing the nonlinear relationships among the parameters, each equation is estimated by nonlinear Least Squares. Lastly, the model is estimated as a restricted system by nonlinear Least Squares and nonlinear SUR. In all cases, parameters are endogenously estimated. Irrespective of the estimation method, the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 24 publications
2
60
0
5
Order By: Relevance
“…Empirical studies by Dechow et al (1999), Myers (1999), and Callen and Morel (2001) and Morel (2003) provide extensive empirical evidence that the Ohlson (1995) model is of limited empirical validity. One possible reason is the restrictive assumption of the Ohlson model that accounting is unbiased, whereas US GAAP is strongly biased towards conservatism.…”
mentioning
confidence: 99%
“…Empirical studies by Dechow et al (1999), Myers (1999), and Callen and Morel (2001) and Morel (2003) provide extensive empirical evidence that the Ohlson (1995) model is of limited empirical validity. One possible reason is the restrictive assumption of the Ohlson model that accounting is unbiased, whereas US GAAP is strongly biased towards conservatism.…”
mentioning
confidence: 99%
“…As stated by Callen and Segal (2005: 409), "studies by Dechow et al (1999), Myers (1999), Callen and Morel (2001) and Morel (2003) The major contribution of this study is to test whether EFI is relevant in explaining current stock prices and future stock returns. We therefore enhance existing linear information models by integrating EFI and testing the models' ability to explain current stock prices and predict future stock performance.…”
Section: Introductionmentioning
confidence: 91%
“…Using Myers (1999) approach Callen & Morel (2001), revised LID hypothesis and includes AR (2) structure in abnormal earnings and found that the intrinsic value on the revised structure basis is not superior tointrinsic value based on the AR (1) structure. Dechow et al (1999) and Myers (1999) were weak in estimation of thecost of capital to calculate abnormal earnings (Morel, 2003) and corrected this drawback by estimating risk premium and firm level persistence parameters, which allows them to changecross-sectional wise cost of capital. She also examined the predictive ability of O'95 by risk premium and earnings Many studies discussed conservatism with LID (Feltham &Ohlson, 1995;Myers, 1999;Ashton & Wang, 2013;Clubb, 2013;Skogsvik & Juettner-Nauroth, 2013).…”
Section: Asian Journal Of Finance and Accountingmentioning
confidence: 99%
“…Predictive linkassesses the forecasting capacity of the model to predict future abnormal earnings (Eq 6&7) (Giner & Lniguez, 2006). O'95 is a landmark study in accounting research not only because it associate accounting numbers with stock prices in a systematic manner but it also widely accepted in empirical studies (Collins et al, 1999;Morel, 2003;Barth et al, 2005;). According to Callen & Morel (2001), three prominent reasons appear behind it.…”
Section: Empirical Studies Based On O'95mentioning
confidence: 99%